2020
DOI: 10.1007/s11240-020-01781-x
|View full text |Cite
|
Sign up to set email alerts
|

A fast, simple, high efficient and one-step generation of composite cucumber plants with transgenic roots by Agrobacterium rhizogenes-mediated transformation

Abstract: Agrobacterium rhizogenes-mediated transformation is widely used in different species with various purposes. The development of composite plants (wild-type shoot with transgenic roots) has been a milestone for functional characterization of genes. Previously, composite plants were generated by two steps from inducing of hairy roots to growing in the growth medium. Hairy roots were induced in an induction medium and the growth of composite plants generated were in another different growth medium. The composite p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 43 publications
2
29
1
Order By: Relevance
“…The maps of all constructs and sequences are shown in Figure S5. The binary vector pGSE401-KtRfg1 ( Figure S5a), pCAMBIA1305 ( Figure S5b) and pYGUS1305 ( Figure S5c) were introduced into A. rhizogenes strain K599 [34,35] by electroporation, respectively. K599 strain was cultured as described previously [35].…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maps of all constructs and sequences are shown in Figure S5. The binary vector pGSE401-KtRfg1 ( Figure S5a), pCAMBIA1305 ( Figure S5b) and pYGUS1305 ( Figure S5c) were introduced into A. rhizogenes strain K599 [34,35] by electroporation, respectively. K599 strain was cultured as described previously [35].…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…The binary vector pGSE401-KtRfg1 ( Figure S5a), pCAMBIA1305 ( Figure S5b) and pYGUS1305 ( Figure S5c) were introduced into A. rhizogenes strain K599 [34,35] by electroporation, respectively. K599 strain was cultured as described previously [35]. To make the inoculation medium, fresh culture K599 bacteria (HGCI) grown on the plate was resuspended using 0.25× Gamborg B-5 basal medium to OD600 ≈ 0.6-1.0.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Therefore, A . tumefaciens -mediated transformation is time-consuming, recalcitrant nature and not efficient enough to allow the high-throughput for functional genomic research [ 23 ]. Besides A .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the hairy root transformation has been widely utilized to validate and optimize induced mutagenesis by the CRISPR/Cas9 system (Michno et al, 2015;Du et al, 2016;Jacobs and Martin, 2016;Li et al, 2019;Le et al, 2020). Both in vitro and in vivo cucumber hairy root cultures have been established for different research purposes (Shi and Lindemann, 2006;Anuar et al, 2011;Fan et al, 2020). However, the application of cucumber hairy root transformation for genome editing using CRISPR/Cas systems has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…However, the application of cucumber hairy root transformation for genome editing using CRISPR/Cas systems has not been reported yet. Moreover, it has been reported that hairy root induction frequency is affected by cucumber varieties, bacterial strains, and transformation methods (JingLong et al, 2017;Fan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%